JUNIOR-SENIOR HIGH SCHOOL BASED ON PESANTREN BOARDING SYSTEM - Abdul Rohman (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2014)
The study is aimed to uncover that a boarding system in junior-senior high school (SMP-SMA) Semesta Billingual Boarding School (BBS) Semarang adopted the pesantren style. This is evidenced by the fact that, like pesantren, the typical of boarding school in BBS Semarang puts more emphasis on strengthening the affective (akhlāq) aspects, because of; 1) the curriculum of all subjects in school mutually integrated, 2) the curriculum design by the development of self-habituation, 3) design through creating climate and culture, 4) constitute the hidden curriculum, 5) more